Treatment Of Textile Wastewater Using Hibiscus Rosa-Sinensis (Bunga Raya) Leaf Extract As Caogulant - Abdul Aziz, Hamidi; Sim, Yee Ling; Umar, Muhammad (2012)
Treatment of textile wastewater is one of the largest problems faced by the textile manufacturers in Malaysia. This study was conducted to investigate the efficiency of Hibiscus rosa-sinensis or Bunga Raya leaf extract as coagulant and coagulant aid with poly-aluminium chloride (PACl) for the treatment of textile wastewater. Evaluation was based on the removal of chemical oxygen demand (COD), suspended solids (SS), color as well as the influence on zeta potential and particle size using standard jar test apparatus.